2012
DOI: 10.1186/1744-8603-8-21
|View full text |Cite
|
Sign up to set email alerts
|

Facilitators and barriers to accessing reproductive health care for migrant beer promoters in Cambodia, Laos, Thailand and Vietnam: A mixed methods study

Abstract: BackgroundThe purpose of the research was to assess access to sexual and reproductive health services for migrant women who work as beer promoters. This mixed methods research was conducted in Phnom Penh, Cambodia, Bangkok, Thailand, Vientiane, Laos, and Hanoi, Vietnam during 2010 to 2011.MethodsFocus groups were held with beer promoters and separate focus groups or interviews with key informants to explore the factors affecting beer promoters’ access to health care institutions for reproductive health care. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
65
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(73 citation statements)
references
References 19 publications
5
65
2
1
Order By: Relevance
“…Based on the sexual experience of the group, 45.2 percent had sexual intercourse with three or more people during their lifetime which was consistent to H. Yang et al's study [19]. Furthermore, the majority of respondents never had sex with their clients neither voluntarily nor beneficially that was similar to Webber study and H. Yang et al study [19,20]. There were 25.2 percent respondents who did not use a condom as a protection which consistent with 2011 Cambodia STI survey among female beer promoters [21] In terms of attitude levels toward using a condom, 72.8 percent of female beer promoters had a neutral attitude about using condom, while 19.6 percent of them had a negative attitude.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Based on the sexual experience of the group, 45.2 percent had sexual intercourse with three or more people during their lifetime which was consistent to H. Yang et al's study [19]. Furthermore, the majority of respondents never had sex with their clients neither voluntarily nor beneficially that was similar to Webber study and H. Yang et al study [19,20]. There were 25.2 percent respondents who did not use a condom as a protection which consistent with 2011 Cambodia STI survey among female beer promoters [21] In terms of attitude levels toward using a condom, 72.8 percent of female beer promoters had a neutral attitude about using condom, while 19.6 percent of them had a negative attitude.…”
Section: Discussionsupporting
confidence: 83%
“…The study showed that most participants worked as part-time beer promoters (78.3 percent) which was inconsistent with Webber et al's study [20], while majority of respondents worked as full-time beer promoters (83 percent). This difference might be related to different study areas.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…18 This is further complicated by limited access to sexual and reproductive health services for wives left behind. 19 Positive impacts of husbands' migration include increased accrual of money and material items and improvement in women's decision-making power, particularly for the management of resources and household affairs. 20 Unfortunately, these benefits can also complicate familial relationships and may place a greater burden on women's wellbeing.…”
Section: Introductionmentioning
confidence: 99%
“…However, in 2015 the Thai government attempted to solve these problems by allowing foreigners and migrant workers to purchase a health insurance card with different coverage periods and extended the coverage to the foreign workers. Even a migrant worker who is legally registered with the Ministry of Labour has numerous difficulties in using a government health insurance card, for example the employer confiscates the health card from the workers, or the workers prefer private clinics due to inadequate attention in public hospitals 6 . This obstructs migrant workers from having access to good healthcare.…”
Section: Introductionmentioning
confidence: 99%